Padua Municipal Archives from the 13th to the 20th Centuries: A Case of a Record-Keeping System in Italy - Bonfiglio-Dosio, Giorgetta (Archivaria, 2006)
This research describes the record-keeping systems of Padua’s municipal administration from the 13th to the 20th centuries, i.e., by free commune, Carraresis’ seigniory, public servants of the Republic of Venice, and local administration in the context of the State before and after the national unification (1861, but for Veneto and Padua 1866). The focus is on the analysis of the medieval and modern chancellery, while archives were preserved and kept by corporate bodies charged with public administration, and afterwards bureaucratic and historiographical work carried out in the 19th and the 20th centuries. At this time new management methods, adopted by States created by Napoleon1 and devoted to current archives, influenced historical archives preservation too. This article shows how one Italian city has preserved administrative memory and has created a specific institution to preserve and study historical records. RÉSUMÉ L’auteure décrit dans cet article le système de gestion des documents de 1’administration municipale de Padoue entre le 13e et le 20e siècle, par la commune libre, la seigneurie des Carraresi, les fonctionnaires de la république de Venise, puis 1’administration locale avant et après 1’unification nationale (1861, mais 1866 pour Venise et Padoue). Elle analyse principalement la chancellerie médiévale et moderne, alors que les archives étaient conservées et gardées par des institutions chargées de 1’administration publique, puis le travail bureaucratique et historiographique exécuté aux 19e et 20e siècles. À cette époque, de nouvelles méthodes de gestion, adoptées par les états créés par Napoléon et s’appliquant aux archives courantes, ont également influencé la conservation des archives historiques. Cet article montre comment une ville italienne a conservé sa mémoire administrative et a créé une institution spécifique afin de préserver et d’étudier ses documents historiques.